2016
DOI: 10.2474/trol.11.348
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characteristics of Polyol Ester Type Refrigeration Oils under Refrigerants Atmosphere

Abstract: The authors tested the effects on the tribological characteristics of refrigeration oils under refrigerant atmospheres using a block-on-ring tribometer. Based on the results of a sliding test using the tribometer, it was found that tricresyl phosphate (TCP) in both a polyol ester (POE) and alkylbenzene (AB) oil formed a lubricating film on the sliding surface under R410A atmosphere. Surface analyses revealed that a phosphate film had been formed on the sliding surface. With the POE oil in particular, the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…A block-on-ring tribometer was used [75] to study the tribological characteristics of POE refrigeration oils under HFC-410A and HFC-32 refrigerants. The study concluded that lubricating film formation is affected by both the refrigerants and the base oils.…”
Section: Hydrofluorocarbons (Hfcs)mentioning
confidence: 99%
“…A block-on-ring tribometer was used [75] to study the tribological characteristics of POE refrigeration oils under HFC-410A and HFC-32 refrigerants. The study concluded that lubricating film formation is affected by both the refrigerants and the base oils.…”
Section: Hydrofluorocarbons (Hfcs)mentioning
confidence: 99%
“…Both values were respectively standardized using their average value and standard deviation. Reproduced with permission from ref . Copyright 2023 Japanese Society of Tribologists.…”
Section: Simulationsmentioning
confidence: 99%
“…Further investigations of the tribochemical adsorption and reactions of model gases on iron surfaces were performed by molecular simulations . An atomistic simulator powered by deep learning, MATLANTIS was applied to calculate the stabilized energy by adsorption of model compounds to a clean iron surface.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the potential use of low toxic polyol ester (POE) as drilling mud lubricants has not been given a great attention [3], despite their high performance and biodegradability in general lubricant application [5,6]. Firstly, the oxidation and thermal stability of this type of lubricant has been improved by replacing glycerol with alcohol that does not contain ß-hydrogen atoms [7].…”
Section: Introductionmentioning
confidence: 99%